Pengaruh Kualitas Audit Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Moermahadi Soerja Djanegara (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The purpose of this study is to determine the effect of audit quality on the quality of local government financial statements (LKPD). The quality of the audit is measured by the proxy level of completion or follow-up on the recommendation of the audit result (TLRHP), covering three factors namely the problem of weaknesses of accounting and reporting control systems, budget execution control, internal control structure, and non-compliance factor to the provisions and laws. While the quality of LKPD is measured by the proxy of audit opinion. The study sample used LKPD data from 2011-2015 provinces, cities and districts in Java and Sumatera region covering 279 LKPD (51%) of LKPD population throughout Indonesia. The result of analysis with regression method (least square method) shows that follow-up improvement over weakness of accounting and reporting control, budget execution control, internal control structure, and compliance to regulation and legislation have positive effect to LKPD quality. The greatest influence is shown by improvements over the weaknesses of accounting and reporting control systems. The implications of the research results are to improve the quality of LKPD, monitoring the follow-up improvement on the recommendations of LKPD audit results by BPK auditors should be intensified, with priority monitoring on TLRHP issues of weaknesses of accounting and reporting control systems.